The 2006 Prudhoe Bay shutdown : will recent regulatory changes and BP management reforms prevent future failures? : hearing before the Subcommittee on Oversight and Investigations of the Committee on Energy and Commerce, House of Representatives, One Hundred Tenth Congress, first session, May 16, 2007. - United States. Congress. House. Committee on Energy and Commerce. Subcommittee on Oversight and Investigations. (Washington : U.S. G.P.O. : For sale by the Supt. of Docs., U.S. G.P.O., 2008)
"Serial no. 110-46." Shipping list no.: 2009-0022-P. Distributed to some depository libraries in microfiche. Includes bibliographical references. Mode of access: Internet.